Combined experimental-theoretical approach for the elucidation of mechanisms in chemiluminescence : 1,2-dioxetanone formation with luciferin-like analogs and intramolecular electron transfer during chemiexcitation with in situ generated 1,2-dioxetanes - Melo, Diêgo Ulysses de (2024)
Coordenação de Aperfeiçoamento de Pessoal de Nivel Superior